A new species of the genus Oxycheila (Coleoptera: Cicindelidae) from Bolivia - Šafránek, Ondřej; Amaya, Marcelo (Zootaxa, 2020)
The new species Oxycheila alenatiki sp. nov. (Cicindelidae: Megacephalini) is described from central Bolivia and compared to related species. Colour photographs of habitus and male genitalia of O. alenatiki sp.nov. and related species O. gracillima Bates, 1872 and O. oberthueri Horn, 1897 are compared. A modified taxonomic key to the gracillima species group is provided.